Ameliorative effects of humic acid and L‐tryptophan on enzyme activity, mineral content, biochemical properties, and plant growth of spinach cultivated in saline conditions - Turfan, Nezahat; Kibar, Beyhan; Davletova, Nazakat; Kibar, Hakan (Wiley, 2024)
AbstractSalinity poses a significant abiotic stress that limits plant productivity, thereby posing a serious threat to agricultural sustainability and worldwide food security. Techniques that can overcome this problem are needed. Recent focus has been placed on employing organic substances like humic acid (HA) and amino acids, including L‐tryptophan (L‐TRP), to mitigate the negative effects of salt stress on cultivated plants. Accordingly, in this research, the impact of foliar applications of HA and L‐TRP, both separately and combined, on the growth parameters and biochemical properties of spinach subjected to salt stress was investigated. In the present study, eight treatments (1. control, 2. salt (NaCl), 3. HA, 4. L‐TRP, 5. HA + NaCl, 6. L‐TRP + NaCl, 7. HA + L‐TRP, and 8. HA + L‐TRP + NaCl) were investigated. The study showed that salt stress markedly reduced several growth properties in spinach, including plant height, number of leaves, leaf dimensions, and both fresh and dry weight. Additionally, it significantly lowered contents of chlorophyll (a, b, and total), carotenoid, polyphenol, lutein, anthocyanin, polyphenol oxidase, glycine betaine, relative water content, and the antioxidant enzyme activities (ascorbate peroxidase, catalase, peroxidase, and superoxide dismutase). On the other hand, significant increases were observed in sodium, chlorine, potassium, sulfur, zinc, nickel, proline, malondialdehyde, and hydrogen peroxide levels of spinach with salinity. Individual and combined applications of HA and L‐TRP positively influenced plant growth, relative water content, activities of antioxidant enzyme, chlorophyll, and mineral contents of spinach under both normal and saline conditions. In conclusion, the combined use of HA and L‐TRP under salt stress conditions is promising in mitigating the negative impacts of salinity and can be suggested as an effective alternative approach for cultivating spinach in saline environments.
Keywords: amino acids; biochemical composition; Spinacia oleracea L.; amino acids; foliar application; humic substances; biochemical composition; humic substances; foliar application; Spinacia oleracea L.; Original Article